Experimental study on the shear failure of layered rock bridges - Jianxin Yu; Jianxin Yu; Zhibin Zhou; Huanchun Liu; Lianhao Zhou; Zhenzhen Li; Long Cheng; Long Cheng (Frontiers in Earth Science, 2023)
The structural face of rock plays a decisive role in the stability of geotechnical engineering, and the mechanism of failure destabilization of layered rock masses is still unclear. By preparing rock-like materials, shear failure tests on layered rock masses were carried out under different bedding dip angles, different rock bridge width, different normal forces, and forward and reverse shear effects. With the increase in the rock bridge width, the influence of the joint inclination angle on the shear failure process of the rock sample decreases; the peak shear strength of the specimen is the largest when the joint inclination angle is 60°, followed by 90°, 30° and 0° from large to small; the failure mode in forward shear is mainly tensile failure, and the failure mode in reversed shear is mainly shear failure; the peak number of acoustic emission events is proportional to the joint inclination angle and the rock bridge width of the specimen, and the number of acoustic emission events is proportional to the joint inclination angle and the rock bridge width of the specimen. The number of acoustic emission peak events is proportional to the bedding angle of the sample and the width of the rock bridge. The peak number of acoustic emission events in the reverse shear of the layered rock mass is greater than that in the forward shear. The angle of the lamina and the width of the rock bridge are both important factors affecting the strength of the rock. The results of this study provide a basis for identifying the shear failure mechanism of rock bridge in layered rock masses.